Benefit-sharing in Environmental Governance Local Experiences of a Global Concept - Parks, Louisa (Earthscan Studies in Natural Resource Management, 2020)
Taking a bottom-up perspective, this book explores local framings of a wide range of issues related to benefit-sharing, a growing concept in global environmental governance. Benefit-sharing in Environmental Governance draws on original case studies from South Africa, Namibia, Greece, Argentina, and Malaysia to shed light on what benefit-sharing looks like from the local viewpoint. These local-level case studies move away from the idea of benefit-sharing as defined by a single international organization or treaty. Rather, they reflect different situations where benefit-sharing has been considered, including agriculture, access to land and plants, wildlife management, and extractives industries. Common themes in the experiences of local communities form the basis for an exploration of spaces for local voices at the international level in the Convention on Biological Diversity (CBD), often argued to be the most open arena to non-state actors, and therefore vital to how local voices may be included at the global level. The book analyzes the decisions of the CBD parties to produce an in-depth reflection on how this arena builds and delimits spaces for the expression of local community themes, and paths for local community participation including community protocols. The book then situates the bottom-up findings in the wider debate about global civil society and deliberative democracy in environmental governance. This interdisciplinary book will be of great interest to students and scholars of environmental politics, environmental law, political ecology and global governance, as well as practitioners and policymakers involved in multilateral environmental agreements.